Water Quality of Batang Lupar Estuary, Sarawak - Faddrine Holt Ajon, Anak Jang (Universiti Malaysia Sarawak, UNIMAS, 2012)
This study was conducted to determine the water quality status in Batang Lupar estuary of Sarawak. A sampling was carried out at Batang Lupar estuary on 17 th December 2012. A total of six sampling stations with 2 km distance between two adjacent stations was chosen. Both in-situ and ex-situ physico-chemical parameters of water were measured and analysed. This included depth (7.40 ± 0.00 m to 10.50 ± 0.00 m), water temperature (29.9 ± 0.05 °C to 31.4 ± 4.35 °C), pH (7.35 ± 0.00 to pH 7.44 ± 0.00), DO (6.29 ± 0.08 mg/L to 8.16 ± 0.23 mg/L), salinity (11.5 ± 0.00 PSU to 18.7 ± 0.00 PSU), conductivity (19.60 ± 0.02 µS to 28.26 ± 0.01 µS), turbidity (87 ± 7.76 FTU to 992 ± 13.85 FTU), water transparency (11 ± 0.00 mm to 24 ± 0.00 mm), chlorophylla (0.4418 ± 0.00 µg/L to 3.4403 ± 0.30 µg/L), TSS (1358.0 ± 20.29 mg/L to 19348.6 ± 1746.89 mg/L), BOD5 (1.63 ± 0.12 mg/L to 3.63 ± 0.28 mg/L), Nitrite (0.009 ± 0.00 mg/L to 0.012 ± 0.00 mg/L), Nitrate (0.02 ± 0.00 mg/L to 0.06 ± 0.02 mg/L), Ammonia-Nitrogen (0.32 ± 0.24 mg/L to 2.04 ± 0.12 mg/L), and Orthophosphate (0.03 ± 0.01 mg/L to 0.10 ± 0.09 mg/L). Other than that, heavy metals were analyzed too including As (0.1420 ± 0.09 mg/L to 0.1808 ± 0.03 mg/L), Cu (0.0073 ± 0.00 mg/L to 0.0110 ± 0.00 mg/L), Pb (undetected), Mn (0.0098 ± 0.00 mg/L to 1.1769 ± 0.48 mg/L), Ni (0.0054 ± 0.00 mg/L to 0.0162 ± 0.00 mg/L) and Zn (0.0063 ± 0.00 mg/L to 0.1228 ± 0.04 mg/L). Nitrite, Nitrate, Zn and DO were within the standard range proposed by MWQS of DOE. The water quality of Batang Lupar Estuary was clean and safe. Human residential along the river and other activities such as logging and agriculture are amongst the factor influencing the water quality of Batang Lupar Estuary.